Vliv sterilizace formaldehydem, gama zářením a etylenoxidem na vlastnosti polyetylenových komponent kloubních náhrad - Fulín, P; Pokorný, D; Slouf, M; Vacková, T; Dybal, J; Sosna, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2014)
PURPOSE OF THE STUDY: Each method of sterilisation has some effect on the structure and properties of UHMWPE and thus also on joint replacement longevity. This study was designed to compare, using objective methods of measurement, several kinds of sterilisation and to recommend the one which has the best prospect for making joint replacements last longer. MATERIAL AND METHODS: Two groups of UHMWPE samples were tested. Group 1 included virgin GUR 1020 polyethylene, non-modified and non-sterilised (Meditech, Germany). Group 2 comprised of three sets of samples sterilised with formaldehyde, gamma irradiation and ethylene oxide, respectively. In both groups, physicochemical properties were assessed by infrared spectroscopy (IR), and the oxidation (OI) and trans-vinyl (VI) indices, which show the degree of oxidation of a material, were determined. Free-radical concentrations were measured by the method of electron spin resonance (ESR). The mechanical properties of each sample were studied using small punch tests (SPT) and testing microhardness (MH). Any change in mechanical properties can affect, to various degrees, the quality and longevity of a prosthetic joint. RESULTS: The samples sterilised by gamma irradiation showed higher values of both the OI (0.37) and the VI index (0.038) than the other samples (OI, 0.02 to 0.05 and VI, 0). Also, the free-radical concentration was detectable only in the gamma-sterilised sample. Values obtained for mechanical properties were as follows: peak load in the range of 58.48 N (gamma irradiation) to 59.60 N (ethylene oxide); ultimate load in the range of 46.69 N (gamma irradiation) to 57.50 N (ethylene oxide); ultimate displacement in the range of 4.29 mm (gamma irradiation) to 4.58 mm (virgin polyethylene and formaldehyde); and work to failure in the range of 185.18 mJ (gamma irradiation) to 205.89 mJ (virgin polyethylene). Microhardness values were obtained in the following ranges: 41.2 to 44.6 MPa (virgin polyethylene); 40.2 to 44.1 MPa (formaldehyde); 46.1 to 49.3 MPa (gamma irradiation); and 40.3 to 44.2 MPa (ethylene oxide). DISCUSSION: The samples sterilised with formaldehyde and ethylene oxide have mechanical properties very similar to virgin polyethylene, they are not damaged by oxidation and do not contain free radicals. Owing to these characteristics, the immediate and long-term oxidation stability of the three samples is higher. The sample sterilised by gamma irradiation showed the presence of free radicals and immediate and long-term oxidative degradation. This results in the deterioration of mechanical properties and the growth of crystallinity due to enhanced oxidation and leads to higher polyethylene microhardness. CONCLUSIONS: Sterilisation with gamma irradiation results in oxidative degradation and mechanical property deterioration, which is one of the potential risks of a shorter life span of joint replacements. The use of ethylene oxide or formaldehyde does not change polymer properties nor has any effect on oxidation of materials. Therefore, a longer life expectancy of the joint replacements sterilised with ethylene oxide can be expected. The life span of their joint replacements is a key issue for the patients. Prosthetic joint loosening is painful and the patient often requires re-implantation. A higher number of re-implantations is associated with higher costs for the institution involved and, consequently, for the whole health care system. Although this study basically deals with chemical issues, it informs the surgeon of the latest developments leading to the improvement of implanted materials, which can increase the life expectancy of joint replacements and patients' satisfaction.
Keywords: protézy kloubů; Formaldehyde; ethylenoxid; lidé; Spectrophotometry, Infrared; záření gama; polyethylen; selhání protézy; Ethylene Oxide; Sterilization; Humans; formaldehyd; Polyethylene; artroplastiky kloubů; srovnávací výzkum účinnosti; Joint Prosthesis; spektrofotometrie infračervená; testování materiálů; sterilizace; Arthroplasty, Replacement; Gamma Rays; Materials Testing; Prosthesis Failure; Comparative Effectiveness Research